Evolutionary Divergence of Duplicated Hsf Genes in Populus - Liu, Bobin (Cells, 2019)
Heat shock transcription factors (Hsfs), which function as the activator of heat shock proteins (Hsps), play multiple roles in response to environmental stress and the development of plants. The Hsf family had experienced gene expansion via whole-genome duplication from a single cell algae to higher plants. However, how the Hsf gene family went through evolutionary divergence after genome duplication is unknown. As a model wood species, Populus trichocarpa is widely distributed in North America with various ecological and climatic environments. In this study, we used P. trichocarpa as materials and identified the expression divergence of the PtHsf gene family in developmental processes, such as dormant bud formation and opening, catkins development, and in response to environments. Through the co-expression network, we further discovered the divergent co-expressed genes that related to the functional divergence of PtHsfs. Then, we studied the alternative splicing events, single nucleotide polymorphism distribution and tertiary structures of members of the PtHsf gene family. In addition to expression divergence, we uncovered the evolutionary divergence in the protein level which may be important to new function formations and for survival in changing environments. This study comprehensively analyzed the evolutionary divergence of a member of the PtHsf gene family after genome duplication, paving the way for further gene function analysis and genetic engineering.